2017
DOI: 10.5812/hepatmon.57917
|View full text |Cite
|
Sign up to set email alerts
|

Transient Elastography in Methotrexate Administered Patients

Abstract: Background: As Methotrexate (MTX) may induce liver side effects or damage, evaluating the liver of the consumers of this drug by a noninvasive method, such as FibroScan, may be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In the present study, significant and severe fibrosis was observed in 3 patients. In a similar study, out of 160 patients with long-term RA treatment with MTX with a median cumulative dose of 4225 mg, only 12 of them reported significant fibrosis (21). Therefore, the occurrence of severe renal fibrosis measured in TE is not as common as in our study.…”
Section: Evaluation Of Tgfβ Gene Expressionsupporting
confidence: 45%
See 1 more Smart Citation
“…In the present study, significant and severe fibrosis was observed in 3 patients. In a similar study, out of 160 patients with long-term RA treatment with MTX with a median cumulative dose of 4225 mg, only 12 of them reported significant fibrosis (21). Therefore, the occurrence of severe renal fibrosis measured in TE is not as common as in our study.…”
Section: Evaluation Of Tgfβ Gene Expressionsupporting
confidence: 45%
“…In the study of Kumar et al (15), which included 160 patients with RA treated with low-dose MTX for more than five years, no significant relationship was observed between the duration of use and the cumulative dose of renal fibrosis. Mansour-Ghanaei et al (21) also examined the kidney of 101 patients with psoriasis and RA by TE treated with methotrexate for at least two years and did not find a significant relationship between the presence of renal fibrosis with cumulative dose and duration of methotrexate use. Unlike the previous two studies, obese and alcoholics were also examined in this study.…”
Section: Evaluation Of Tgfβ Gene Expressionmentioning
confidence: 99%
“…We present further convincing data supporting the use of non-invasive markers of fibrosis and steatosis to guide the treatment of rheumatologic and dermatologic diseases. TE has been used to advise which patients on MTX have already developed fibrosis ( 12 14 ). However, our study shows that an increased CAP score can advise which patients are at increased risk of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Transient elastography (TE) is a non-invasive measure of hepatic fibrosis that has been used in patients on MTX ( 12 14 ). TE measures the stiffness (or elasticity) of the hepatic parenchyma using both ultrasound and low-frequency elastic waves produced by an ultrasound vibrator applied to the right upper quadrant to measure the propagation speed of a wave using a pulse-echo ultrasound ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Hepatic fibrosis was staged to convert Fibroscan results (measured in kPa) to the Metavir scoring system as follows: F0 (no fibrosis), F1 (mild fibrosis without septa), F2 (moderate fibrosis with few septa), F3 (severe fibrosis with numerous septa without cirrhosis), and F4 (cirrhosis or advanced scarring of the liver). [ 18 ]…”
Section: Methodsmentioning
confidence: 99%